Kepercayaan Kepada Yang Ghaib: Tumpuan Khusus Kepada Peranan Makhluk Jin dalam Kehidupan Makhluk Manusia - Stapa, Zakaria (Jurnal Usuluddin, 1998)
As well as formulating and covering the real scope and exact definition of the term aqidah or faith from the Islamic perspective, this paper focuses on two main theme as follows: first, the analysis of the nature and the habitual inclination of the jinn, which also includes the iblis, syaitan and ifrit. Second, the discussion pertaining to the classic and eternal enmity between these beings and the human creature, whereby its effect are visible in the lives of the human beings since the beginning of time. Then, in this enmity, as it can be seen clearly, especially in this age, for instance, the humans are on the losing side, and are losing the battle that broke out from this eternal enmity.